2007
DOI: 10.1007/s00125-007-0771-4
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of low plasma thiamine concentration in diabetes linked to a marker of vascular disease

Abstract: Aims/hypothesis To assess thiamine status by analysis of plasma, erythrocytes and urine in type 1 and type 2 diabetic patients and links to markers of vascular dysfunction. Methods Diabetic patients (26 type 1 and 48 type 2) with and without microalbuminuria and 20 normal healthy control volunteers were recruited. Erythrocyte activity of transketolase, the concentrations of thiamine and related phosphorylated metabolites in plasma, erythrocytes and urine, and markers of metabolic control and vascular dysfuncti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
232
1
14

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 239 publications
(253 citation statements)
references
References 43 publications
6
232
1
14
Order By: Relevance
“…14 respectively. 51 Oxythiamine is not detectable by the thiochrome assay as it lacks the 4-aminopyrimidinyl moiety required for thiochrome formation.…”
Section: Assay Of Thiamine and Tpp By The Hplc Thiochrome Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…14 respectively. 51 Oxythiamine is not detectable by the thiochrome assay as it lacks the 4-aminopyrimidinyl moiety required for thiochrome formation.…”
Section: Assay Of Thiamine and Tpp By The Hplc Thiochrome Methodsmentioning
confidence: 98%
“…Recent studies in diabetes and CKD suggest there are also abnormalities of thiamine transport due to tissue-specific down regulation of thiamine transporters. 14,37,47 Measurement of renal clearance of thiamine is a sensitive clinical marker of this. 14 Red blood cell transketolase activity is valuable to assess impact on the pentosephosphate pathway and αETKA to explore cause of transketolase activity deficit.…”
Section: In Clinical Translation Dietary Deficiency Of Thiamine -Leamentioning
confidence: 99%
“…Interestingly, increased clearance was prevented by high-dose thiamine supplementation [26] . Thiamine renal clearance is also increased in subjects with T1DM (by 24-fold) and T2DM (by 16-fold) [24] . Further changes of thiamine metabolism probably occur with the development of chronic diabetic microvascular complications namely diabetic nephropathy together with chronic kidney disease (CKD).…”
Section: Consequences Of Hyperglycemia For Thiamine Availabilitymentioning
confidence: 93%
“…Patients with type 1 and 2 diabetes mellitus (T1DM and T2DM) do not have a marked thiamine deficiency [conventionally defined as an increase of TKT activity in red blood cells (RBC) higher than 15% after addition of saturating amount of TDP]. However, plasma thiamine levels in diabetics are decreased by 75% compared to healthy subjects [24] . RFC-1 and THTR1 protein expression in RBCs obtained from diabetic patients (both T1DM and T2DM) is higher than in healthy subjects [24] .…”
Section: Thiamine Mishandling In Diabetesmentioning
confidence: 99%
“…However, a number of studies found an altered thiamine handling in the kidneys of diabetic patients [16][17][18]. Benfotiamine, (S-benzoylthiamine-Omonophosphate), a derivative of the vitamin B1 or thiamine, has a much higher bioavailability than thiamine and, as a result, accumulates in the target tissues much more than thiamine itself [15,19,20].…”
Section: Introductionmentioning
confidence: 99%